2017
DOI: 10.1002/cpdd.344
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Verapamil, a P‐Glycoprotein Inhibitor, on the Pharmacokinetics of Peficitinib, an Orally Administered, Once‐Daily JAK Inhibitor

Abstract: Peficitinib is an orally administered, once-daily Janus kinase inhibitor currently in development for the treatment of rheumatoid arthritis. It has been shown to be a P-glycoprotein (P-gp) substrate in vitro. The effects of verapamil, an inhibitor of the efflux pump P-gp, on the pharmacokinetic profile of peficitinib were assessed in this open-label, single-center, single-sequence, crossover drug-interaction study. Twenty-four healthy volunteers received a single 150-mg dose of peficitinib on days 1 and 12 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…2008; Zhu et al. 2017; Chen et al. 2018), and CYP3A4 also participates in the metabolism of oridonin (Xu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008; Zhu et al. 2017; Chen et al. 2018), and CYP3A4 also participates in the metabolism of oridonin (Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…2008; Zhu et al. 2017; Chen et al. 2018), therefore, the absorption of some drugs with poor oral bioavailability could be enhanced (Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Peficitinib, a new orally JAK blocker that inhibits JAK1, JAK2, JAK3, TYK2 and with a mild selectivity for JAK3 (Zhu et al, 2017). Metabolism and pharmacokinetics of peficitinib are similar to other JAK inhibitors, in which peficitinib was absorbed rapidly with small food effects after single doses (Cao et al, 2016).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…14 However, a recent study of peficitinib in combination with verapamil (P-glycoprotein inhibitor) showed increased exposure of peficitinib and its metabolites, suggesting that P-glycoprotein may be involved in peficitinib transport. 15 While the peficitinib PK profile has been described in healthy subjects, 11 it is important to determine the impact of potential comorbidities, such as liver disease, on peficitinib exposure. The burden of liver disease related to hepatitis infection remains high, 16 and there is a rise in nonalcoholic fatty liver disease and its histological phenotype, nonalcoholic steatohepatitis (NASH), which are related to increased obesity and can progress to chronic liver disease.…”
mentioning
confidence: 99%